Monocyte function in the acquired immune deficiency syndrome. Defective chemotaxis. - Smith, P D (1984)
The ineffective immune response in patients with the acquired immune deficiency syndrome (AIDS) contributes to severe and widespread infections and unrestricted growth by certain tumors. To determine whether monocyte dysfunction contributes to this immunosuppressed condition, we investigated monocyte chemotaxis in patients with AIDS. Using three different chemotactic stimuli, N-formylmethionylleucylphenylalanine, lymphocyte-derived chemotactic factor, and C5a des Arg, we studied the chemotactic responses of monocytes from seven homosexual men with AIDS, three homosexuals with lymphadenopathy and an abnormal immunological profile, seven healthy homosexual men, and 23 heterosexual control individuals. Monocytes from each of the AIDS patients with Kaposi's sarcoma and/or opportunistic infection exhibited a marked reduction in chemotaxis to all stimuli compared with the healthy control subjects. The reduced chemotactic responses were observed over a wide range of concentrations for each stimulus. Monocytes from AIDS patients who had clinically apparent opportunistic infection(s) exhibited a greater reduction in monocyte migration to all three stimuli than monocytes from the AIDS patient with only Kaposi's sarcoma. Monocytes from each of three homosexuals with lymphadenopathy and an abnormal immunological profile exhibited decreased chemotactic responses that were intermediate between those of the AIDS patients and the healthy heterosexual control subjects. In contrast to these findings, monocytes from each of seven healthy homosexuals exhibited normal chemotactic responses to the same stimuli. In addition, monocytes from AIDS patients exhibited reduced chemotaxis to soluble products of Giardia lamblia, one of several protozoan parasites prevalent in AIDS patients. Thus the immune abnormality in AIDS, previously thought to involve only the T-, B-, and natural killer lymphocytes, extends to the monocyte-macrophage. Defective monocyte migratory function may contribute to the depressed inflammatory response to certain organisms and to the apparent unrestricted growth of certain neoplasms in patients with AIDS.